The Filipino Male as “Macho-Machunurin”: Bringing Men and Masculinities in Gender and Development Studies - Angeles, Leonora C. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
As Filipino feminist scholars move beyond the stage of "women as victim, men as problem" discourse in gender studies, there is a need to discuss the place of men in gender and development studies. Academics and advocates note the pitfalls of "women-focused" and "women-only" development interventions, citing women-focused programs that succeed mostly in shifting the burden of responsibility for contraception, parenting and housework on women. There is a need to take into account the experiences of different varieties of men from marginal groups based on class, ethnicity, age, generation and position in the life cycle as gender roles react to socio-economic changes: As it is, men and masculinity have not been adequately theorized. Expressions of Filipino masculinities within the Filipino family, market place, work environment, and marital relations are complex.1he inclusion of men and masculinities in gender studies has so far been confined to the unmasking of the "problematic male." By uncovering the multiple layers and forms of masculinities, feminist scholars and advocates could come up with more strategic development plans and programs and more successfully reorder gender relations.
Keywords: Men; Masculinity Discourse